TECHNICAL AND TACTICAL INDICATORS OF COMPETITIVE ACTIVITIES OF JUDOISTES OF 16-17 YEARS OF AGE (Physical Culture and Sport: Scientific Perspective, 2025)
The article analyzes the analysis of technical and tactical indicators of competitive activity of judoists of 16-17 years old for further individualization of the training process. To achieve the goal the analysis of video recordings of competitive activity of judoists was used in the research. When analyzing video recordings of competitive activity 3 fights of each of sportswomen of the control (n=10) and experimental (n=10) groups were analyzed. In total 30 fights of sportswomen of the control and 30 fights of sportswomen of the experimental groups were analyzed. The following techniques were found to be highly effective in both groups: arm turn and landing. Also, such throws as a hook from the inside under the p/n, a hook from the inside under the o/n, with the foot emphasis in the stomach have an efficiency of 25-33% and very often these throws are included in combinations of techniques. It was established that the inverts were performed the greatest number of times, but had a low efficiency (control group 11%; experimental group - 17%). The second technical action which was more often performed by sportswomen of both groups is a hold (control group - 30 %; experimental - 27 %) which had rather high efficiency (control group - 62 %; experimental - 67 %) in comparison with other technical actions. The analysis of technical and tactical indicators revealed that combinations of techniques and counter moves were performed almost the same number of times by athletes of both groups (control group 52 and 48 %; experimental group - 44 and 56 %). But counter moves were more effective (control group - 60 %; experimental group - 50 %). It was found that the athletes of both groups received remarks for not fighting (control group - 13 remarks; experimental group - 11) and pulling into the floor (control group - 4 remarks; experimental group - 5). It was found that most of the fights of athletes of both groups ended early, only one fight of each group was held in additional time.
Keywords: judo; judoists; sportswomen; technical and tactical indicators; competitive activity; analysis; technical actions; questionnaire